Rancang Bangun Aplikasi Kelayakan Pinjaman Pada Koperasi Sejahtera Tani Nusantara (KOSTIN) - Tambunan, Andrie Dermanto; Soebijono, Tony; Oktaviani, Oktaviani (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Koperasi Sejahtera Tani Nusantara (KOSTIN) a savings and loan cooperative that aims to provide venture capital lending services for the city of Pekanbaru. Currently  realization of the loan assessment Koperasi Sejahtera Tani Nusantara still subjective and the manual is just to provide an assessment whether  a prospective customer is given a loan or not. Assessments are subjective and the manual, also influenced from the subjective to the trust factor against the prospective customer. This assessment resulted in some customers' arrears exceeded installment maturing resulting in  capital turnover noncurrent. To resolve the  problems above, so engineering designs of customer lending eligibility application is made using 7P method of assessing prospective customers from the side: personality, party, purpose, prospect, payment, profitabillity, protection. With this application is expected to co-operatives can determine the suitability of prospective customers in obtaining credit and are expected to reduce the number of customers in arrears at a later date. Based on the results of trials that have been done can be concluded that the application complies with the expected goals. The app has been able to assess the feasibility of loans to help decide the realization of the loan.Keywords  Application, Cooperative, Assessment, Worthiness, Loan, Recording, Payment